군산시 대기오염물질 배출량 조사에 관한 연구(2015~2019) - 박상훈(Sang-Hun Park); 김득수(Deug-Soo Kim); 김성천(Seong-Cheon Kim) (Daehan hwan'gyeong gonghag hoeji, 2023)
목적 : 본 연구에서는 2015년부터 2019년까지 5년간의 군산시의 대기오염물질 배출량 자료를 이용하여 연도별 배출량 현황을 분석하였다. 또한 군산시와 인접한 지역(전주시, 익산시)의 배출량 특성을 파악하고자 한다. 방법 : 환경부 국가미세먼지정보센터에서 제공하는 대기정책지원시스템(Clean Air Policy Support System, CAPSS)의 대기오염물질 배출량 자료(2015~2019)를 이용하여 군산시 대기오염물질 배출량 현황(CO, NOx, SOx, PM10, VOCs, NH3)을 분석하였다. 또한 군산시와 인접한 지역(전주시, 익산시)의 배출량 특성을 파악하였다. 결과 및 토의 : 군산시는 CO(자동차등록대수), PM10(화물 수송량) NH3(비료사용농경지, 분뇨관리)배출량은 증가하였다. NOx(유리 제품생산) SOx{유리(탄소 제거공정)}, VOCs(위스키 등 독주)배출량은 감소하였다. 배출량 특성에서 CO와 NOx는 도로 이동오염원과 비도로이동오염원(레저, 화물)이며, SOx는 생산공정{유리 (탄소 제거공정)}과 에너지산업 연소(민간 발전시설)이다. PM10은 비도로 이동오염원(선박, 화물), 비산먼지(도로 재비산먼지, 건설공사, 농업)이며, VOCs는 생산공정에서 식음료 가공(위스키 등 독주)과 유기용제 사용은 도장시설(선박 제조)이다. NH3는 농업(비료사용농경지, 분뇨관리)과 생산공정(암모니아소비)이다. 배출량 특성 비교에서 군산시(CO, NOx, SOx, VOCs), 전주시(PM10), 익산시(NH3)로 높게 나타났다. 결론 : 군산시의 대기오염물질 배출량 비율은 VOCs > NOx > CO > SOx > NH3 > PM10의 순으로 나타났다. 배출량 특성 비교에서 군산시, 전주시, 익산시는 NOx와 NH3는 동일하며 CO, SOx, PM10, VOCs는 서로 다른 특성을 보였다. 이러한 경우는 산업단지 규모 및 지역의 지리적인 특성, 경제구조, 인구 등의 영향을 받은 것으로 사료된다. Objectives : In this study, the emission status by year was analyzed using the air pollutant emission data of Gunsan for 5 years from 2015 to 2019. In addition, it is intended to identify the emission characteristics of (Jeonju and Iksan). . Methods : Using the air pollutant emission data of the Clean Air Policy Support System(CAPSS) provided by the Ministry of Environment's National Fine Dust Information Center, the status of air pollutant emissions(CO, NOx, SOx, PM10, VOCs, NH3) in Gunsan was analyzed. Results and Discussion : In Gunsan, CO(car registration number), PM10(cargo transport volume) NH3(farmland using fertilizer, manure management) emissions increased. NOx(production of glass products) SOx{glass (carbon removal process)} and VOCs(whiskey, etc) emissions were reduced. In the emission characteristics, CO and NOx are mainly road transport and non-road transport pollutants(leisure, cargo) and SOx is production process{glass(carbon removal process)} and energy industry combustion(private power plant). PM10 is a non-road moving pollutant(ship, cargo), scattering dust(road scattering dust, construction work, agriculture), and VOCs are food and beverage processing(whiskey, etc) and organic solvent in the production process painting facility (ship manufacturing). NH3 is agricultural(fertilized cropland, manure management) and production processes(ammonia consumption). In the comparison of emission characteristics, Gunsan(CO, NOx, SOx, VOCs), Jeonju (PM10), Iksan(NH3) were high. Conclusions : The emission rate of air pollutants in Gunsan was in the order of VOCs > NOx > CO > SOx > NH3 > PM10. In the comparison of emissions characteristics, Gunsan, Jeonju and Iksan showed the same in NOx and NH3, but different in CO, SOx, PM10 and VOCs characteristics. This case is considered to be influenced by the size of the industrial complex, geographical characteristics of the region, economic structure, and population. KCI Citation Count: 3